Ban on bacterium that beats plant poison - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Millions of animals die each year after eating poisonous plants. The problem is particularly severe in the arid tropics when there is a dearth of normal feed supplies, and cattle are tempted to eat shrubs and trees that they would normally avoid....